СОЦИАЛЬНО - ПСИХОЛОГИЧЕСКИЕ АСПЕКТЫ ИСПОЛЬЗОВАНИЯ РЕКЛАМЫ НА МЕДИА - РЫНКЕ. (Journal of Economic Research & Business Administration, 2016)
In the competitive market for today's businesses more successful business development is necessary to study additional areas in marketing. These concerns and the psychology of advertising as a tool to influence the consumer.